Strategi Implementasi Kebijakan Pengurangan Emisi melalui Infrastruktur Sepeda di Perkotaan Indonesia di Kota Bekasi - Setiabudi, Adi; Nuriman, Eki Jaki; Hidayat, Rahmat; Dewi, Maya Puspita; Muksin, Nani Nurani (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Motorized vehicle-based transportation is one of the primary contributors to carbon emissions in urban areas of Indonesia. Bekasi City, as one of Jakarta's buffer cities, faces challenges in reducing carbon emissions due to the dominance of motorized vehicles and inadequate transportation infrastructure. This study aims to analyze the policy implementation strategies for reducing carbon emissions through the development of bicycle infrastructure, focusing on the integration of bike lanes, supporting facilities, and public transportation. The findings reveal that the adoption of bicycles in Bekasi remains low due to a lack of infrastructure support and public awareness. This study recommends strategic measures such as enhancing coordination among stakeholders, allocating adequate budgets, and conducting public awareness campaigns to promote bicycles as a primary mode of transportation. With an integrated approach, this policy is expected to support carbon emission reductions in Bekasi and other cities in Indonesia.